La Asociación Sud-Americana de Paz Universal y Ángela Oliveira Cézar: pacifismo, activismo trasnacional y «diplomacia femenina» - Paula Bruno (Les Cahiers ALHIM)
This article analyzes the Asociación Sud-Americana de Paz Universal (Buenos Aires, 1907) as a space for female action that embraced the ideals of internationalist pacifism. The association was projected and created by the Argentinean Ángela Oliveira Cézar (1860-1940), who became a reference figure of international pacifism in the passage from the 19th to the 20th century. Based on the itinerary of its founder and the dynamics of the association and resorting to different types of sources –documentation of the group (statutes, correspondence, books published), national and international periodical press, official documentation, personal correspondence– the article studies the possibilities and limits of Latin American women in undertaking actions motivated by American fraternity and international pacifism and the articulation between the local, regional and transnational repercussions of their initiatives. It also focuses on the actions promoted by the association in contexts of conflict and fraternity between countries of the American continent –such as the placement of the Christ of the Andes on the border between Chile and Argentina, symbolic corollary of the signing of the Pact of May 1902–. The essay is part of the «New Diplomatic History», a developing area that has given rise to the study of women in transnational scenes.